Three new species of Myrsidea (Phthiraptera: Menoponidae) from New Zealand passerines (Aves: Passeriformes) - Sychra, Oldrich; Kolencik, Stanislav; Palma, Ricardo L. (Zootaxa, 2016)
Myrsidea ivanliteraki new species, M. novaeseelandiae new species, and M. hihi new species are described and illustrated from New Zealand birds, with Gymnorhina tibicen, Anthornis melanura and Notiomystis cincta as type hosts respectively. Also, Myrsidea vincula is redescribed and illustrated from one sample ex Strepera fuliginosa from Australia. Keys for the identification of females and males of the five species of Myrsidea recorded from New Zealand are also given.